Motivations for (non)participation in population-based health studies among the elderly – comparison of participants and nonparticipants of a prospective study on influenza vaccination. Issue 1 (December 2017) - Akmatov, Manas; Jentsch, Leonhard; Riese, Peggy; May, Marcus; Ahmed, Malik; Werner, Damaris; Rösel, Anja; Prokein, Jana; Bernemann, Inga; Klopp, Norman; Prochnow, Blair; Illig, Thomas; et al.
Abstract Background Participation in epidemiological studies has strongly declined in recent years. We examined the reasons for (non)participation in population-based health studies among participants and nonparticipants of a prospective study on influenza vaccination among the elderly. Methods Males and females between 65 and 80 years of age (N =  5582) were randomly selected from the residents' registration office in Hannover, Germany, and were invited to participate in a study featuring vaccination with a seasonal adjuvanted influenza vaccine (Fluad™, Novartis) including five follow-up visits (day 0, 1/3, 7, 21, 70 with respect to vaccination). A 24-item nonresponder questionnaire, including 10 items on reasons for participating in a hypothetical health study, was mailed to 1500 randomly selected nonparticipants. The same 10 items were included in the end-of-study questionnaire administered to the participants in the vaccination study (n =  200). Logistic regression analysis with backward elimination was used to identify the reasons most strongly associated with nonparticipation. Results Five hundred thirty-one (35%) nonparticipants and 200 participants (100%) returned the respective questionnaires. Nonparticipation was associated with a lower interest in obtaining personal health information (OR = 3.32) and a preference for less invasive (OR = 3.01) and less time-demanding (OR = 2.19) studies. Responses to other items, e.g. regarding altruistic motives, monetary compensation, general interest of the study, or study approval through ethics committee and data security authority, did not differ between participants and nonparticipants. Conclusions Participation rates in health studies among elderly individuals could potentially be improved by reducing interventions and time demand, for instance by implementing methods of self-sampling and remote data collection. Trial registration No.1100359 (ClinicalTrials.gov, date of registration: 09.02.2015).